1990
DOI: 10.1016/0042-6822(90)90385-5
|View full text |Cite
|
Sign up to set email alerts
|

Processing and intracellular transport of rubella virus structural proteins in COS cells

Abstract: Plasmids encoding rubella virus (RV) structural proteins C-E2-E1, E2-E1, E2, and E1 have been constructed in the eukaryotic expression vector pCMV5. The processing and intracellular transport of these proteins have been examined by transient expression of the cDNAs in COS cells. Compared to alphaviruses, processing of RV glycoprotein moieties occurred relatively slowly and the transport of glycoproteins E2 and E1 to the plasma membrane was inefficient. Indirect immunofluorescence revealed that the majority of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 35 publications
5
101
0
Order By: Relevance
“…Immunofluorescence studies revealed that the mutant C protein was present in the cells as discrete bodies and clusters of bodies; the C_s~ protein appears to dimerize as normal, and it is possible that it is also forming larger aggregates, or associating with other, as yet unidentified subcellular structures. GiUam and coworkers (Hobman et al, 1990;McDonald et al, 1991) have reported that the normal C is distributed throughout the cytoplasm, with or without the E2 protein. It is difficult to explain these findings in the light of both our own immunofluoresence studies and the results of our in vitro and in vivo membrane association assays.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Immunofluorescence studies revealed that the mutant C protein was present in the cells as discrete bodies and clusters of bodies; the C_s~ protein appears to dimerize as normal, and it is possible that it is also forming larger aggregates, or associating with other, as yet unidentified subcellular structures. GiUam and coworkers (Hobman et al, 1990;McDonald et al, 1991) have reported that the normal C is distributed throughout the cytoplasm, with or without the E2 protein. It is difficult to explain these findings in the light of both our own immunofluoresence studies and the results of our in vitro and in vivo membrane association assays.…”
Section: Discussionmentioning
confidence: 99%
“…These biochemical data are confirmed, to some extent, by immunofluorescence studies of the location of the RV structural proteins when expressed in various combina- tions. These suggest that E2 and E1 co-localize in a Golgi-like compartment in COS cells when expressed together, with or without the C protein (Hobman et al, 1990; our own unpublished observations). In addition, E2, when expressed alone, was found distributed in both the ER and the Golgi complex (Hobman et al, 1990; our own unpublished observations).…”
Section: E2 Is Required For Transport Of E1 To the Golgi Apparatus Bumentioning
confidence: 98%
See 3 more Smart Citations